Anti-inflammatory effects of Phyllanthus amarus Schum. & Thonn. through inhibition of NF-κB, MAPK, and PI3K-Akt signaling pathways in LPS-induced human macrophages - Hemavathy Harikrishnan; Ibrahim Jantan; Md. Areeful Haque; Endang Kumolosasi (BMC, 2018)
Abstract Background Phyllanthus amarus has been used widely in various traditional medicines to treat swelling, sores, jaundice, inflammatory diseases, kidney disorders, diabetes and viral hepatitis, while its pharmacological and biochemical mechanisms underlying its anti-inflammatory properties have not been well investigated. The present study was carried out to investigate the effects of 80% ethanolic extract of P. amarus on pro-inflammatory mediators release in nuclear factor-kappa B (NF-кB), mitogen activated protein kinase (MAPK) and phosphatidylinositol 3-kinase/Akt (PI3K-Akt) signaling activation in lipopolysaccharide (LPS)-induced U937 human macrophages. Methods The release of prostaglandin E2 (PGE2) and pro-inflammatory cytokines, tumor necrosis factor (TNF)-α and interleukin (IL)-1β in a culture supernatant was determined by ELISA. Determination of cyclooxygenase-2 (COX-2) protein and the activation of MAPKs molecules (JNK, ERK and p38 MAPK), NF-κB and Akt in LPS-induced U937 human macrophages were investigated by immunoblot technique. The relative gene expression levels of COX-2 and pro-inflammatory cytokines were measured by using qRT-PCR. The major metabolites of P. amarus were qualitatively and quantitatively analyzed in the extract by using validated reversed-phase high performance liquid chromatography (HPLC) methods. Results P. amarus extract significantly inhibited the production of pro-inflammatory mediators (TNF-α, IL-1β, PGE2) and COX-2 protein expression in LPS-induced U937 human macrophages. P. amarus-pretreatment also significantly downregulated the increased mRNA transcription of pro-inflammatory markers (TNF-α, IL-1β, and COX-2) in respective LPS-induced U937 macrophages. It downregulated the phosphorylation of NF-κB (p65), IκBα, and IKKα/β and restored the degradation of IκBα, and attenuated the expression of Akt, JNK, ERK, and p38 MAPKs phosphorylation in a dose-dependent manner. P. amarus extract also downregulated the expression of upstream signaling molecules, TLR4 and MyD88, which play major role in activation of NF-κB, MAPK and PI3K-Akt signaling pathways. The quantitative amounts of lignans, phyllanthin, hypophyllahtin and niranthin, and polyphenols, gallic acid, geraniin, corilagin, and ellagic acid in the extract were determined by HPLC analysis. Conclusion The study revealed that P. amarus targeted the NF-κB, MAPK and PI3K-Akt signaling pathways to exert its anti- inflammatory effects by downregulating the prospective inflammatory signaling mediators.